The Relationship between Level of Voluntary Disclosure in Internet and Information Asymmetry in Companies Listed on the Tehran Stock Exchange - Pour, Omid Ahad; Imanzadeh, Peyman (International Journal of Economics and Financial Issues, 2017)
The purpose of this study was to investigate the relationship between Internet-based disclosures with information asymmetry of listed companies in Tehran stock exchange between 2009 and 2014. In the present study, the sampling, purposive sampling method, which is used on the systematic elimination of 85 companies were selected. In order to assess the exact impact of each factor on the dependent variables, each of these components in main hypotheses were tested and handed intended. The results showed an inverse relationship between the level of voluntary disclosure on the Internet and meaningful information asymmetry exists. Keywords: Voluntary Disclosure in Internet, Information Asymmetry, Stock Exchange JEL Classifications: F31, L86